2019
DOI: 10.1055/s-0039-1697643
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Diabetes and Hearing Loss

Abstract: Hearing loss is a highly prevalent chronic condition. In addition to age, sex, noise exposure, and genetic predisposition, cardiovascular disease and its antecedents may precipitate hearing loss. Of emerging interest is the connection between diabetes and auditory dysfunction. Cross-sectional studies consistently suggest that prevalence of hearing loss is higher in persons with diabetes compared with those without diabetes, especially among younger persons. Furthermore, longitudinal studies have demonstrated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Hearing impairment, both in high-frequency and low-to midfrequency ranges, is more common in people with diabetes than in those without, with stronger associations found in studies of younger people (80). Proposed pathophysiologic mechanisms include the combined contributions of hyperglycemia and oxidative stress to cochlear microangiopathy and auditory neuropathy (81).…”
Section: Sensory Impairmentmentioning
confidence: 99%
“…Hearing impairment, both in high-frequency and low-to midfrequency ranges, is more common in people with diabetes than in those without, with stronger associations found in studies of younger people (80). Proposed pathophysiologic mechanisms include the combined contributions of hyperglycemia and oxidative stress to cochlear microangiopathy and auditory neuropathy (81).…”
Section: Sensory Impairmentmentioning
confidence: 99%
“…Results of studies performed globally have been conflicting with regard to HI and duration of DM, [7,13,17,21] gender, [5,13,22,23] patient age [13,24,25] and type of antidiabetic therapy. [4,12,[26][27][28] Similarly, findings with regard to the relationship between DM-related complications and HI have also been inconclusive, with some studies demonstrating a positive relationship between DM-related neuropathy [12,22] and retinopathy [21] and HI, while others showed none.…”
Section: Researchmentioning
confidence: 99%
“…Numerous clinical and experimental studies have shown the effect of diabetes on ABR recordings. These changes include an elevation in the hearing threshold and an increase in waves latency as well as a decrease in the amplitude with changes in waveforms [35,36].…”
Section: Discussionmentioning
confidence: 99%